Goles de infância: práticas da docência e das crianças em uma escola municipal de educação infantil - Queila Cristina de Oliveira (2019)
This study is based on the investigation of how the pedagogical practices of three teachers are developed, considering the participation of the child. The research was carried out in a Municipal School of Early Childhood Education (EMEI), a public institution, located in a neighborhood in the northeast region of Belo Horizonte-MG, where the author also worked as a teacher. In this context, there was interlocution with teachers and, approximately, 40 children, in the age group of 04 and 05 years. The data generation and analysis process was based on the phenomenological, ethnographic and auto-ethnographic approaches. To do so, the procedures and resources used included: Logbook, class recordings, video; recordings, in audio, of conversations and semi-structured interviews with the subjects involved; as well as written artifacts used and / or produced at that school. Throughout this work, a pedagogical product called "Ateliê Narrativo" was also developed, which includes a continuous formation of the teachers of the EMEI, with a view to bringing reverberations in the context. Some references in the fields of Education, Anthropology, Sociology of Childhood, Philosophy, Languages and Psychology corroborate with this study, such as: Freire (1987, 1995, 1996, 1997); Oliveira-Formosinho (2007; 2009); Tardif and Raymond (2000); Tardif, Lessard and Lahaye (1991); André (2012); Geertz (2008); Alanen (2001); Sirota (2001); Corsaro (2011); Walter Benjamin (1987; 2009); Larrosa (2002; 2011); Vygotsky (2007; 2009; 2014); Bakhtin (2011); Bachelard (1988); Rancière (2015); and Paul Zumthor (2010, 2014). This research pointed to some conclusions among which I emphasize: teachers' listening to children's voices, through a dialogical perspective, comprises one of the main elements that mobilize pedagogical practices that promote the child's participation in educational processes.